The Impact of COVID-19 Pandemic on Managerial Accounting and Its Adjustments in Financial Markets - Mabelle A. Atienza; Almighty C. Tabuena (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This study aimed to identify the impact of the COVID-19 pandemic on managerial accounting and its adjustments in financial markets to help business society deal with their businesses and companies during the pandemic. This study was conducted in one of the cities in the Metropolitan Manila in Quezon City, Philippines, employing the descriptive design under the qualitative research method through an interview protocol and online form methods with accountants, managers, and business owners using Fiedler’s Contingency Theory. This research initiative is a great help for those who are suffering in their business, especially managers, accountants, and business owners. Managerial accounting in the financial markets has had a lot of difficulties since this pandemic occurred. In this case, businesses were not prepared for the advent of the COVID-19 pandemic. Some business owners had to close their businesses for three months because of the outbreak. Business owners are taking steps to become affable and open to the consumers that might purchase their products. Despite the pandemic, company owners are determined to stay open. They knew how to cope with scammers, especially those who ran an online company during this pandemic crisis. Keywords: adjustment, contingency theory, COVID-19, financial market, impact, managerial accounting